The Potential of Natural Enemies as Biological Control Agents for Various Pests on Water Spinach (Ipomoea aquatica F.) - Wahyuni, Srilah Nora; Ilwati, Uun; Akram, Ahdiatsa Hairi; Dewi, Pervitara Arum; Sarjan, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Arthropods have the potential as biological control agents for various pests in kale plants. Some arthropod species have potential as natural enemies for biological control of plant pests due to their abundance and availability in the ecosystem. Some natural enemy arthropods consist of insects and spiders. Natural enemies found in the location of West Lombok District, NTB act as predators and parasitoids of pests on kale plants. The number of orders found were Araneae, Coleoptera, Hemiptera, Odonata and Hymenoptera. Four orders act as predators and one order, Hymenoptera as parasitoids. Natural enemy arthropods found that have the potential as natural enemies of pests in kale plants were found as many as 10 species, namely Argiope catenulate, Cicurina sp.., Oxyopes attenuates, Lepthypanthes tenuis, Cheilomenes sexmaculata, Coreus Marginatus, Leptoglossus occidentali sp., Onychogomphus forcipatus, Agriocnemis pieris, and Doryctobracon areolatus. While in Ogan Ilir District, South Sumatra, 1 species was found that acts as a natural enemy of the Hemiptera order, Gonocerus acuteangulatus.